1960
DOI: 10.1007/bf01377763
|View full text |Cite
|
Sign up to set email alerts
|

Nitrification in soils after different periods of dryness

Abstract: It has been shown (Birch 1) that the longer a soil remains in an air-dry state the greater are the amounts of carbon and nitrogen mineralised on moistening it. These amounts were found to be a significant linear function of the log. of the time the soll was in a dry state prior to moistening. Even short periods in the dry state were sufficient to produce considerably greater amounts of mineral nitrogen, on moistening, than solls that had not been given a preliminary dryäng. Harpstead and Brage s have also repo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
114
0
5

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 342 publications
(129 citation statements)
references
References 7 publications
10
114
0
5
Order By: Relevance
“…For example, water-extractable phosphorus is markedly influenced by even mild drying of soil. It has been known for some time that soil drying can render considerable concentrations of organic carbon soluble in water [54] and a similar effect was recently reported for phosphorus in a wide range of pasture soils from England and Wales [55]. In the latter study, 7 days air drying from approximate field moisture capacity at 30 • C increased concentrations of water-extractable organic phosphorus by up to 1900%.…”
Section: Soilssupporting
confidence: 72%
“…For example, water-extractable phosphorus is markedly influenced by even mild drying of soil. It has been known for some time that soil drying can render considerable concentrations of organic carbon soluble in water [54] and a similar effect was recently reported for phosphorus in a wide range of pasture soils from England and Wales [55]. In the latter study, 7 days air drying from approximate field moisture capacity at 30 • C increased concentrations of water-extractable organic phosphorus by up to 1900%.…”
Section: Soilssupporting
confidence: 72%
“…The importance of this is considerable in those parts of the tropics with clearly defined wet and dry seasons. The classical studies of Birch (1958Birch ( , 1960 showed that the flush of mineral N at the start of the wet season in East Africa was a result of the population dynamics of the soil microbes. Immediately after rain, the young population increases rapidly, utilizing relatively easily decomposable materials.…”
Section: Nutrient Supply and Watermentioning
confidence: 99%
“…The non-linear inorganic nitrogen behaviour led to include into the model scheme also other threshold mechanisms (U min , U nitr , U imm and U denitr ) in order to simulate soil processes 'pulse' behaviour, previously observed in several Mediterranean and semi-arid environments (Birch 1959(Birch , 1960(Birch , and 1964Mummey et al, 1994, Schiwinning et al 2004. The sensitivity analysis, generally pointed out that thresholds as influential on nitrogen simulation.…”
Section: Discussionmentioning
confidence: 99%
“…Simulated mineralization seems to be highest immediately after the summer drought period ( 'Birch effect', Birch 1959, 1960, and 1964, when the soil moisture content reaches approximately 50% of the soil field capacity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation